2018
DOI: 10.1007/s00248-018-1210-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Infection and Reproductive Manipulations of Wolbachia in Homona magnanima (Lepidoptera: Tortricidae)

Abstract: Endosymbiotic bacterium Wolbachia interacts with host in either a mutualistic or parasitic manner. Wolbachia is frequently identified in various arthropod species, and to date, Wolbachia infections have been detected in different insects. Here, we found a triple Wolbachia infection in Homona magnanima, a serious tea pest, and investigated the effects of three infecting Wolbachia strains (wHm-a, -b, and -c) on the host. Starting with the triple-infected host line (W), which was collected in western Tokyo in 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…We have not found other reports of sex-specific Wolbachia distribution in other populations, as is the case with single infected P. proximus . However, Arai et al [ 44 ] reported, in an experiment on subdividing triple infection, a 79% transmission rate for the w Hm-b strain in males of Homona magnanima (Lepidoptera: Tortricidae) versus a rate of 100% in daughters. Dutton and Sinkins [ 45 ], in double infected Aedes albopictus , found w AlbA loss in males.…”
Section: Discussionmentioning
confidence: 99%
“…We have not found other reports of sex-specific Wolbachia distribution in other populations, as is the case with single infected P. proximus . However, Arai et al [ 44 ] reported, in an experiment on subdividing triple infection, a 79% transmission rate for the w Hm-b strain in males of Homona magnanima (Lepidoptera: Tortricidae) versus a rate of 100% in daughters. Dutton and Sinkins [ 45 ], in double infected Aedes albopictus , found w AlbA loss in males.…”
Section: Discussionmentioning
confidence: 99%
“…This initial characterization of Wolbachia and CI in Cu. pipiens opened the floodgates, with many ensuing studies reporting cases of CI-inducing Wolbachia in Diptera ( Baton et al, 2013 ; Bian et al, 2013 ; Hoffmann et al, 1986 ; Riegler and Stauffer, 2002 ), Hymenoptera ( Betelman et al, 2017 ; Dittmer et al, 2016 ), Coleoptera ( Kajtoch and Kotásková, 2018 ), Hemiptera ( Ju et al, 2017 ; Ramírez-Puebla et al, 2016 ), Orthoptera ( Martínez-Rodríguez and Bella, 2018 ), Lepidoptera ( Arai et al, 2019 ; Hornett et al, 2008 ), Thysanoptera ( Nguyen et al, 2017 ), Acari ( Gotoh et al, 2007 ; Gotoh et al, 2003 ; Vala et al, 2002 ), Isopoda ( Cordaux et al, 2012 ; Sicard et al, 2014 ), and Arachnids ( Curry et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is inevitable that this process of infection and spread sometimes occurs in the context of other vertically-transmitted endosymbionts, either through co-infection of the same host individual, or through interactions of differentially-infected individuals in the host population. As molecular techniques for characterizing bacterial communities continue to improve, evidence is accumulating that symbiont diversity within and among hosts likely greater than previously appreciated [1214]. While the dynamics of interacting symbionts have been considered theoretically in various contexts [e.g., 15,16], empirical work has been quite limited, perhaps because the dynamic phase of symbiont spread in host populations can be temporally transient [10,17].…”
Section: Introductionmentioning
confidence: 99%